2016
DOI: 10.1093/jjco/hyw129
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative change in neutrophil–lymphocyte ratio predicts the overall survival of patients with bladder cancer undergoing radical cystectomy

Abstract: Perioperative changes in neutrophil-lymphocyte ratio are significantly associated with overall survival in patients with bladder cancer undergoing radical cystectomy. Follow-up of the neutrophil-lymphocyte ratio change may be useful for the clinical management of patients after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…An increase of NLR or PLR during or after therapy was associated with poorer total and disease-free survival (DFS) in several studies ( 70 , 72 , 73 ). Simultaneously, patients had a better prognosis if NLR decreased after chemotherapy or targeted therapy ( 69 , 73 ). Therefore, also dynamic changes of PLR and NLR seem to be prognostically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…An increase of NLR or PLR during or after therapy was associated with poorer total and disease-free survival (DFS) in several studies ( 70 , 72 , 73 ). Simultaneously, patients had a better prognosis if NLR decreased after chemotherapy or targeted therapy ( 69 , 73 ). Therefore, also dynamic changes of PLR and NLR seem to be prognostically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…This also did not evaluate patients who received NAC. In another study, perioperative changes in NLR were significantly associated with OS in patients undergoing radical cystectomy, and patients with a high post-operative NLR who had a decrease in NLR after adjuvant chemotherapy had improved outcomes [ 27 ]. However, the clinical applicability of this data is limited by the fact that current guidelines recommend NAC rather than adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that a pre-treatment NLR < 2.5 could predict for better progression-free survival, cancer-specific survival, overall survival, and pathologic response in MIBC patients undergoing NAC [ 26 ]. Although perioperative changes in NLR are associated with survival, the change in NLR during NAC and its impact on outcomes is not fully understood [ 27 ]. The objectives of this study were to evaluate the prognostic role of baseline NLR on outcomes and the impact of the change in NLR over the course of NAC on outcomes in patients with MIBC.…”
Section: Introductionmentioning
confidence: 99%
“…Full-text reviews were performed by the two investigators. Finally, 38 studies were selected for meta-analysis ( Figure 2), including seven articles on TURBT (6,7,(15)(16)(17)(18)(19), 15 on radical cystectomy (8)(9)(10)(11)(12)(20)(21)(22)(23)(24)(25)(26)(27)(28), five on chemotherapy (29)(30)(31)(32)(33), and 11 on nephroureterectomy for upper ureter urothelial carcinoma (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%